Le gant constitutionnel réversible : accessoire de l’uniforme militaire. Regard critique sur la crise constitutionnelle algérienne de 2019 - Mouloud Boumghar (L’Année du Maghreb)
The widespread public rejection for a 5th mandate of the now former President of the Republic Bouteflika gradually leaded to a constant expression of dissent against the Algerian regime as a whole. Much more than a simple political crisis and beyond the future of certain high-ranking officials, legitimacy and legality of the key Algerian State authorities or institutions are challenged, i.e. the Presidency of the Republic, the Government, the Parliament, the Constitutional Council and the ANP Military Staff. Protesters claim a "second Republic" that must be a "civil State, not a military". In front of an increased popular mobilisation and an upgrading level of political grievances, the regime in place took steps that are clearly against the 1996 Constitution or that can be regarded as a constitutional transgression, although it claims to respect the content of the Constitution and protect the institutions. Now, this situation leads Algeria towards a new constitutional deadlock: the de facto prolongation of an interim power at the head of the State for an unlimited duration. The crucial issue in the background is about the role of the army. From now on, in practice and openly, the army holds a monopoly on political decisions, while defending itself not to interfere in politics. The high command refuses the idea of transitional institutions as well as a next election of a constituant assembly in the name of the constitutional order from whom it alleges, wrongly by law, that the army is the guardian. In lieu, the high command tries to impose Presidential elections while increasing repression. But popular mobilisation stands up against any election as long as key figures of the regime will stay in power and until all guarantees for free elections are not fulfilled.